2015
DOI: 10.3892/or.2015.4173
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-144 affects radiotherapy sensitivity by promoting proliferation, migration and invasion of breast cancer cells

Abstract: Radiotherapy resistance remains a major obstacle for patients with breast cancer. miRNAs are important regulators in many biological processes including proliferation, apoptosis, invasion and metastasis and response to treatment in different types of tumors. Here, we describe the role of miRNA-144 in the regulation of radiotherapy sensitivity, migration and invasion of breast cancer cells. The cell survival rate of breast cancer cells was measured by WST-1 assay after irradiation. The caspase-3/-7 activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 37 publications
(29 reference statements)
3
45
0
Order By: Relevance
“…MiR-144 has been reported to affect sensitivity in radiotherapy by promoting proliferation, migration and invasion of breast cancer cells37. Dysregulation of miR-144 has been described in studies of multiple cancers38394041.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-144 has been reported to affect sensitivity in radiotherapy by promoting proliferation, migration and invasion of breast cancer cells37. Dysregulation of miR-144 has been described in studies of multiple cancers38394041.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of miR-144 increased the proliferation rate of tumor cells in the MDA-MB-231 cell line. Additionally, the migration and invasion of tumor cell lines of MDA-MB-231 and SKBR3 were increased by elevated miR-144 expression [148]. Kahraman M et al showed the overexpression of hsa-miR-144-3p and hsa-miR-144-5p in the aggressive subtype triple-negative breast cancer (TNBC).…”
Section: Mir-144 In Breast Cancermentioning
confidence: 99%
“…Real‐time monitoring of miRNAs could refine therapy and identify treatment resistance. Initial studies investigated in vitro response to therapy and a number of therapy‐predictive miRNAs were identified. Studies investigating in vivo response to therapy and circulating miRNAs are limited in that long‐term follow‐up is lacking; however, early results are encouraging ( Table ).…”
Section: Regulation Of Oestrogen Receptor and Her2/neu Expression Andmentioning
confidence: 99%